Lipophilic activated ester prodrug approach for drug delivery to the intestinal lymphatic system - Lee, Jong Bong; Zgair, Atheer; Malec, Jed; Kim, Tae Hwan; Kim, Min Gi; Ali, Joseph; Qin, Chaolong; Feng, Wanshan; Chiang, Manting; Gao, Xizhe; Voronin, Gregory; Garces, Aimie; et al. (Elsevier, 2018)
The intestinal lymphatic system plays an important role in the pathophysiology of multiple diseases including lymphomas, cancer metastasis, autoimmune diseases, and human immunodeficiency virus (HIV) infection. It is thus an important compartment for delivery of drugs in order to treat diseases associated with the lymphatic system. Lipophilic prodrug approaches have been used in the past to take advantage of the intestinal lymphatic transport processes to deliver drugs to the intestinal lymphatics. Most of the approaches previously adopted were based on very bulky prodrug moieties such as those mimicking triglycerides (TG). We now report a study in which a lipophilic prodrug approach was used to efficiently deliver bexarotene (BEX) and retinoic acid (RA) to the intestinal lymphatic system using activated ester prodrugs. A range of carboxylic ester prodrugs of BEX were designed and synthesised and all of the esters showed improved association with chylomicrons, which indicated an improved potential for delivery to the intestinal lymphatic system. The conversion rate of the prodrugs to BEX was the main determinant in delivery of BEX to the intestinal lymphatics, and activated ester prodrugs were prepared to enhance the conversion rate. As a result, an 4-(hydroxymethyl)-1,3-dioxol-2-one ester prodrug of BEX was able to increase the exposure of the mesenteric lymph nodes (MLNs) to BEX 17-fold compared to when BEX itself was administered. The activated ester prodrug approach was also applied to another drug, RA, where the exposure of the MLNs was increased 2.4-fold through the application of a similar cyclic activated prodrug. Synergism between BEX and RA was also demonstrated in vitro by cell growth inhibition assays using lymphoma cell lines. In conclusion, the activated ester prodrug approach results in efficient delivery of drugs to the intestinal lymphatic system, which could benefit patients affected by a large number of pathological conditions.